An Evaluation of the Genetic Variability of Tilapia guineensis Populations Based on Microsatellite Markers (Nigerian Journal of Physiological Sciences, 2025)
Improvement of aquaculture production, conservation and stock management of T. guineensis species are important. The genetic variation of this specie as well as their cross-breeding pattern and growth performance were assessed. One hundred and fifty live samples with average weights of TG (21.90g and 31.60g) for females and males, respectively, were collected from three different water bodies. DNA was extracted using the phenol-chloroform isoamyl alcohol method from randomly selected fish populations. The quality and quantity of DNA were determined using a spectrophotometer. Microsatellites were amplified, and PAGE electrophoresis was analyzed using PopGene version 3.6 software. The DNA concentrations ranged from 100.36 ng/l to 3889.40 ng/l with purity values of 1.69 to 2.00. The partial regions of the gene fish populations amplified were polymorphic, with an average of two allele differences in frequency. The values of gene diversity, Polymorphic information Content and inbreeding coefficient were 0.41, 0.30, and -0.41, respectively. Observed heterozygosity was higher than expected heterozygosity in the fish populations. The genetic variations observed among the crossbreeds emphasized the importance of selective breeding for fast growth by increasing productivity, but pure lines should be maintained so that it forms part of the base line population and avoid inbreeding over time.